Bee venom phospholipase A2 as a membrane-binding vector for cell surface display or internalization of soluble proteins. (15th June 2016) - Babon, Aurélie; Wurceldorf, Thibault; Almunia, Christine; Pichard, Sylvain; Chenal, Alexandre; Buhot, Cécile; Beaumelle, Bruno; Gillet, Daniel
Abstract: We showed that bee venom phospholipase A2 can be used as a membrane-binding vector to anchor to the surface of cells a soluble protein fused to its C-terminus. ZZ, a two-domain derivative of staphylococcal protein A capable of binding constant regions of antibodies was fused to the C-terminus of the phospholipase or to a mutant devoid of enzymatic activity. The fusion proteins bound to the surface of cells and could themselves bind IgGs. Their fate depended on the cell type to which they bound. On the A431 carcinoma cell line the proteins remained exposed on the cell surface. In contrast, on human dendritic cells the proteins were internalized into early endosomes.